Influence of social media marketing on modern youth in Russia - Toniaeva, Marina (2020)
The aim of the thesis is to evaluate attitude of Russian youth to marketing in social networks on the platforms YouTube, Instagram and Vkontakte and what key communication activities is better to use to influence the audience of social networks. The theoretical part will reveal the basic concepts of marketing and its role in social networks. Thus, theoretical knowledge was applied in the practical part of the study. To reach the goal of the thesis, assessment of the Russian market and the qualitative method were used. Interviews were conducted with young people aged 18 to 25, in addition, interviews were also taken with experts in the field. This method allows author to evaluate the most influential social networks on consumer behaviour among young people and be aware of their preferences. For research, books, magazines, scientific articles, as well as Internet resources, were used.